Returning to "Ezuversity": Feminism and Emancipation in the Letters of Ezra Pound to Forgotten Modernist Iris Barry, 1916-1917 - Camacho, Paula (Atlantis. Journal of the Spanish Association for Anglo-American Studies, 2019)
At the beginning of the twentieth century, many young male and female poets attended “Ezuversity,” that is, Ezra Pound’s programme through which he educated them on the art of reading and writing. This study focuses on the case of Iris Barry (1895-1969), the English poet, novelist, film critic and forgotten modernist pioneer, to whom Pound sent a series of letters at the beginning of the twentieth century encouraging her to emancipate herself and avoid marriage. It also analyses “The Ezra Pound Period,” a text written by Barry and published in the Bookman in 1931, which serves as a response to the poet’s letters and instruction. The aim of this article is to contribute to feminist modernist studies by rescuing Barry from oblivion and by highlighting Pound’s promotion and support of many women writers who would later play a significant role in literary modernism. Keywords: Iris Barry; Ezra Pound; “Ezuversity”; literary modernism; feminism; women’s emancipation